﹣1的4次幂-[1-﹙1-0.5×1/3﹚]×6
1个回答
﹣1的4次幂-[1-﹙1-0.5×1/3﹚]×6
=-1-(1-5/6)*6
=-1-1/6*6
=-1-1
=-2
相关问题
-1的4次幂-(1-0.5)的2次幂×1∕3×[2-(-3)的2次幂]
(1-2的2次幂分之1)×(1-3的2次幂分之1)×(1-4的2次幂分之1)×.×(1-99的2次幂
(1)6×0.3= (2) 0.5÷ 1 7 = (3) 1 4 - 1 5 = (4)15×0.4= (5) 1.6×
1.(4)-1的4次方-(2的3次方-0.5×3分之1)×(-6)²
0×1×2×3+1=1=1^2 1×2×3×4+1=25=5^2 2×3×4×5+1=121=11^2 3×4×5×6+
口算:(1)0.1×0.1=(2)0.24×0.5=(3)5.4+3.6=(4)1.25-0.25=(5)6.45×0.
(-1 100次幂)×5+(-2 4次幂)÷4
观察下列各式:1×2×3×4+1=25=5的两次方,2×3×4×5+1=121=11的两次方,3×4×5×6+1=361
-17×1/4-0.47×1/6+(-0.47)×5/6+3/4×(-17)=多少
2.5×5= 10+0.4= 2.5×0.4= 7.1×0.2= 1÷0.1= 3.6÷0.4= 0.2×3.1= 4.